EFFECT OF COUNTRY ALMOND (Terminalia catappa) MEAL ON REPRODUCTIVE INDICES OF AFRICAN CATFISH (Clarias gariepinus, BURCHELL 1822) IN MAIDUGURI, NIGERIA - YAGANA, A.; DIYAWARE, M. Y.; IBRAHIM, I.; MOHAMMED, Z. B. (Nigerian Journal of Fisheries, 2020)
The effects of Terminalia catappa meal on reproductive performance of Clarias gariepinus were carried out. A total of seventy-two (72) broodfish were randomly divided into four experimental groups, each having male and female in the ratio of 1:1 per treatment, replicated 3 times. The fish were fed with feeds containing T. catappa meal at the concentrations of 0 (Control), 10, 20 and 30% inclusion levels. Three each of the females and males broodfish were randomly collected from each treatment group and used for evaluating the reproductive performances. The result shows no significant differences (P > 0.05) between the fertilization and hatching rate of the fry among. However, the fry from brood fish treated with 30% T. catappa leave meal showed a higher survival rate. The fertilization rate, fecundity rate and gonadosomatic index were better in the control diet. Terminalia catappa leaves meal did not have significant effect on the reproductive indices of C. gariepinus.